Trajectory Planning and Motion Recognition for Rhythmic Movements of a Biped Robot - Za'Balawi, Ibrahim Ismail (2009)
In this research, Response Surface based Methodology (RSM-based) is proposed as a systematic methodology to characterize the parameters of the implemented CPG. The CPG has been constructed using four coupled non-linear oscillators of Van Der Pol (VDP) connected to five-link biped robot through simple Proportional Derivative (PD) closed-loop control system. The coupled non-linear oscillators generate joint angles trajectories (hips and knees) for the five-link biped robot. RSM-based has screened the interactive effects of VDP parameters on biped\'s locomotion responses